Effects of organic fertilizers on organic carbon accumulation in alkalized saline soil and silage maize yield - Ji, Lidong; Li, Lei; Wang, Rui; Xu, Xing; Zhang, Fengju; Mao, Guilian; Wang, Teng (International Journal of Agricultural and Biological Engineering, 2024)
To understand the combined effect of organic and chemical fertilizers on soil carbon emissions and carbon balance of a farmland ecosystem, this study investigated the organic fertilizer nitrogen replacing different proportions of chemical fertilizer nitrogen. The results showed that, compared to F100, the O15F85 treatment increased the yield and net ecosystem productivity carbon sequestration of silage maize under mild, moderate, and severe salinization levels, as well as the contents of soil organic carbon, microbial carbon, and humin carbon, while reducing plant carbon emissions. The O15F85 treatment did not significantly increase soil carbon emissions (CEC), but O30F70, O45F55 and O100 treatments significantly increased CEC. The soil carbon balance analysis showed that the farmland ecosystem was a “sink” for atmospheric CO2 under each treatment. The O15F85 treatment produced an “excitation effect” to enhance the carbon sink effect of silage maize farmland under mild, moderate and severe salinization levels while maintaining stable production and emissions. Although the O100 treatment increased the carbon sink of farmland under different salinization levels, the yield was significantly reduced and did not represent practical production levels. Correlation analysis showed that soil organic carbon components and ecosystem carbon balance were closely related to soil total salt, pH and bulk density, while soil dissolved organic carbon, humus carbon components and carbon emissions were closely related to soil moisture and temperature. Therefore, the purpose of improving the carbon sink of saline-alkali land can be achieved through soil salt inhibition, soil structure remodeling and water supplement and warming regulation, which provides technical and theoretical support for reducing carbon emissions, achieving carbon neutrality and alleviating global warming. Key words: carbon balance, carbon component, organic carbon, organic substitution, saline-alkali land DOI: 10.25165/j.ijabe.20241702.8258 Citation: Ji L D, Li L, Wang R, Xu X, Zhang F J, Mao G L, et al. Effects of organic fertilizers on organic carbon accumulationin alkalized saline soil and silage maize yield. Int J Agric & Biol Eng, 2024; 17(2): 159–168.